Moral Education According to Buya Hamka (Study of Surah Luqman 12-19 Al-Azhar Tafsir Study) - M. Teguh Ciptadi; Hunainah; Ahmad Syarif (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Moral education according to Buya Hamka, in the study of the interpretation of Surah Luqman 12-19, is a deep effort in understanding and implementing moral values contained in the verses of the Quran. His background was the desire to explain the moral messages contained in Surah Luqman to Muslims. The aim was to provide a deep understanding of the moral values taught by Luqman to his son, as explained in the Quran. The methods used include lectures, demonstrations, and examples, which are described in detail in the Tafsir of Al-Azhar. The results of the study show that moral education according to Hamka includes aspects such as tawhid, relationships with parents, social interaction, and the practice of moral values in everyday life. The conclusion is that moral education according to Hamka has a strong foundation in the Quran and sunnah, and is a guide for Muslims in living a noble moral life. It provides a deep understanding of the importance of morality in human life and how to apply it in daily practice